Megaesophagus - Achalasia: Our experience - Praderi, Luis A.; Balboa, Oscar; Ricciardi, Norma (Cirugía del Uruguay, 1982)
A series of 21 cases of megaesophagus is studied; he benígn form (12 cases) predominating over the severe or sigmoid form which comprises only seven cases. From the analysis of our bibliography we get to he conclusion that this is a rather infrequent affection in Uruguay; perhaps because many of the cases are related as dilations. Chagas disease could not be confirmed as the etiologic factor; not even in those patients coming from the Brazilian border. The stages and priorities of clinícal and paraclinícal testing are chemaized; emphaizing the value of manometry in the differential diagnosis of motor disorders of the esophagus as diffuse spasm. The manometric findings are summed up, giving more importance to the inividual profile than to figures.